PENGADAAN TANAH BERDASARKAN UU. NO. 2 TAHUN 2012 TENTANG PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM (STUDI DI KABUPATEN CILACAP) - Budi Irawan (MIH Unsoed, 2015)
The issuance of Law No. 2 of 2012 on land acquisition (land procurement law) as a legal basis for the government to be doing activities that require land development is expected to ensure legal certainty in land acquisition and sense of fairness to the parties affected by land acquisition. This study aims to analyze the provision of land for the construction of the public interest in Cilacap district and analyze the normative constraints encountered in land acquisition in Cilacap district by Act No. 2 of 2012. The method used is a normative juridical approach uses the method legisme legal positivism, which argues identical with the norms made written and promulgated by agencies or officials of the state. The acquisition of land for public purposes under Law No. 2 of 2012 in Cilacap district includes four (4) phases: Procurement Planning soil; Preparation of the Land Acquisition; Implementation of the Land Acquisition; Submission of Results. Form of compensation in land acquisition is in the form of money, in land, resettlement, ownership or other form approved by both parties. Normative constraints faced is the lack of synchronization and harmonization seen in the regulations implementing the land acquisition law is under preparation that implementation is set in Central Java governor regulation number 18 of 2013 which is about the team and the preparation of the study team. The existence of disharmony in the BAL procurement law is seen also at the time of submission of proof of rights to land at the disposal of land rights can not be contested in the future (Land Acquisition Act article 42 paragraph (2) and (3)), is not exactly. Keyword: liability